MLH1 –93G>A Promoter Polymorphism and the Risk of Microsatellite-Unstable Colorectal Cancer - Raptis, Stavroula; Mrkonjic, Miralem; Green, Roger C.; Pethe, Vaijayanti V.; Monga, Neerav; Chan, Yuen Man; Daftary, Darshana; Dicks, Elizabeth; Younghusband, Banfield H.; Parfrey, Patrick S.; Gallinger, Steven S.; McLaughlin, John R.; et al. (JNCI : Journal of the National Cancer Institute, 2007)
Background Although up to 30% of patients with colorectal cancer have a positive family history of colorectal neoplasia, few colorectal cancers can be explained by mutations in high-penetrance genes. We investigated whether polymorphisms in DNA mismatch repair genes are associated with the risk of colorectal cancer. Methods We genotyped 929 case patients and 1098 control subjects from Ontario and 430 case patients and 275 control subjects from Newfoundland and Labrador for five polymorphisms in the mismatch repair genes MLH1 and MSH2 with the fluorogenic 5′ nuclease assay. Tumor microsatellite instability (MSI) was determined with a polymerase chain reaction–based method; MSI status was assigned as high (MSI-H, ≥30% unstable markers among all markers tested), low (MSI-L, <30% markers unstable), or stable (MSS, no unstable markers). We used unconditional logistic regression to evaluate the association between each polymorphism and colorectal cancer after adjusting for age and sex. The associations between polymorphisms and tumor clinicopathologic features were evaluated with a Pearson's chi-square or Fisher's exact test. All statistical tests were two-sided. Results We observed strong associations between the MLH1 –93G>A polymorphism and MSI-H tumors among case patients from Ontario (P = .001) and Newfoundland (P = .003). When compared with the control populations, homozygosity for the MLH1 –93G>A variant allele was associated with MSI-H tumors among case patients in Ontario (adjusted odds ratio [OR] = 3.23, 95% confidence interval [CI] = 1.65 to 6.30) and in Newfoundland (OR = 8.88, 95% CI = 2.33 to 33.9), as was heterozygosity among case patients in Ontario (OR = 1.84, 95% CI = 1.20 to 2.83) and in Newfoundland (OR = 2.56, 95% CI = 1.14 to 5.75). Genotype frequencies were similar among case patients with MSS and MSI-L tumors and control subjects, and the majority of homozygous variant carriers had MSS tumors. Among case patients from Ontario, an association between the MLH1 –93G>A polymorphism and a strong family history of colorectal cancer (for Amsterdam criteria I and II, P = .004 and P = .02, respectively) was observed. Conclusion In two patient populations, the MLH1 –93G>A polymorphism was associated with an increased risk of MSI-H colorectal cancer.